2009
DOI: 10.1002/jbm.b.31397
|View full text |Cite
|
Sign up to set email alerts
|

In vitro adherence of oral streptococci to zirconia core and veneering glass‐ceramics

Abstract: Plaque formation on dental ceramics may cause gingival inflammation and secondary caries. This in vitro study compared the susceptibility of various dental ceramics to adhere oral streptococci, and verified the influence of substratum surface roughness and surface hydrophobicity. Three zirconia ceramic materials and three veneering glass-ceramics were investigated. Fifteen test specimens were prepared for each material, polished, and surface roughness and hydrophobicity were determined. After incubation with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 37 publications
2
39
0
4
Order By: Relevance
“…Rosentritt conducted an study about S. mutans adhesion on zirconia core and veneering ceramic and reported that there was only little difference between them which is in agreement with our results (16). Ssurface roughness and surface free energy are among the most important factors which may influence the bacterial adhesion (17)(18).…”
Section: Advances In Bioscience and Clinical Medicinesupporting
confidence: 78%
“…Rosentritt conducted an study about S. mutans adhesion on zirconia core and veneering ceramic and reported that there was only little difference between them which is in agreement with our results (16). Ssurface roughness and surface free energy are among the most important factors which may influence the bacterial adhesion (17)(18).…”
Section: Advances In Bioscience and Clinical Medicinesupporting
confidence: 78%
“…This is in contrast to what has been published for metalceramic implant-supported FDPs (43) and also in contrast to studies claiming a high risk of peri-implantitis (59). Ceramic materials have been found to accumulate less plaque and plaque with reduced vitality, compared to other restorative materials (60)(61)(62). The clinical significance is uncertain, however.…”
Section: Discussionmentioning
confidence: 74%
“…In recent years, many evidences demonstrating that the presence of a fixed prosthetic restoration enhances the risk of the onset of periodontal lesions have been collected [2,6]. The awareness of the importance of an abnormal subgingival microbiota in the etiology of periodontal disease and that of adhesion to the hard tissues in dental plaque formation inspired studies aimed to identify materials that were less prone to bacterial colonization [7][8][9] and more suitable to reconstruct normal dental anatomy [1,5]. Although useful to develop optimized materials and techniques, these studies often failed to take into consideration important biological and clinical aspects of the problem and consequently failed to completely unveil the question [6,[10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…However, many evidences that show the existence of a close relationship between the presence of fixed prosthetic restorations and an enhanced risk of periodontal infections have been collected [2,6]. A lot of researches were consequently addressed at studying different dental materials with respect to their susceptibility to colonization by selected bacterial species [7][8][9], their surface characteristics, and many technical aspects related to the possibility to reconstruct normal dental anatomy [1,5]. These studies, nevertheless, frequently do not adequately classify periodontal conditions and confuse mere gingival inflammation and periodontal breakdown, ultimately possibly leading to ambiguous conclusions [6,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%